0294 Baseline Response Speed Predicts Locus Coeruleus Integrity Change After Sleep Deprivation. (27th May 2020) - Quan, P; Lei, H; Wang, J; Liu, W; Zhang, X; Dinges, D; Rao, H
Abstract: Introduction: Locus coeruleus (LC) is the major source of norepinephrine (NE) in the brain, which plays a key role in maintaining arousal and alertness. Sleep loss significantly impairs arousal and alertness. However, it is unknown whether sleep loss disrupts LC integrity, which can be measured non-invasively by diffusion tensor imaging (DTI). In the current study, we used DTI to examine the effects of one night of acute total sleep deprivation (TSD) on fractional anisotropy (FA), an index reflecting fiber density, axonal diameter and myelination. Methods: We analyzed DTI and psychomotor vigilance test (PVT) data from N=54 health adults (23 females, age range 21–50 years) from a well controlled in-laboratory sleep deprivation study. Participants were randomized to either a TSD condition (n=40) without sleep on night 2, or a control condition (n=14) with no sleep loss. Standard DTI scans were conducted on the morning of day 2 and day 3 between 0700h-1000h. The PVT reciprocal response time (RRT) was used to measure individual's response speed at baseline without sleep loss. LC regions-of-interest (ROI) were defined by standard templates from Keren et al. (2009). Imaging data were analyzed using FSL toolbox. Results: For the whole TSD group, no differences were found in the LC FA values before and after sleep deprivation ( p > .2). However, when dividing the TSD group to a slow group and a fast group based on their baseline PVT response speed, significantly increased LC FA were found in the slow group ( p = .007) but not in the fast group ( p > .4). The PVT RRT negatively correlated with LC FA value changes after TSD ( r = -.44, p = .004). No correlations were found between the PVT RRT and LC FA changes in the control group. Conclusion: Our results showed that baseline vigilance response speed correlated with LC integrity change after sleep deprivation, with slower response exhibiting greater changes in LC integrity. These findings support the key role of LC-NE system in the regulation of alertness and arousal. Support: Supported in part by NIH grants R01-HL102119, R01-MH107571, R21-AG051981. CTRC UL1RR024134, and P30-NS045839.